FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN DI BEI - SURYANTO SURYANTO; CHRISTIAN JAYA KUSUMA (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study was to examine whether managerial ownership, institutional ownership, capital structure, profitability, company growth, dividend policy, investment policy, and firm size have affect on firm value for non financial companies listed in Indonesia Stock Exchange. This research used 45 non financial companies listed in Indonesia Stock Exchange, selected using purposive sampling method from periode 2013 until 2016. The data were analyzed using multiple regression analysis method to determine the model of research. The result of this analysis indicated that profitability, company growth, dividend policy, and investment policy had influence on firm value. While managerial ownership, institutional ownership, capital structure, and firm size had no effect on firm value